Karakteristik Fisik Dan Organoleptik Nugget Ayam Petelur Afkir Dengan Penambahan Tepung Ubi Jalar Ungu (Ipomoea batatas) - Aaf Falahudin; Ulfa Indah Laela Rahmah Rahmah; Taufik Ismail (Fakultas Pertanian Universitas Majalengka, 2022)
The purpose of this study was to obtain the optimum formulation using purple sweet potato flour as a filler for the physical and organoleptic properties of rejected laying hen nuggets. This study used a completely randomized design (CRD) with 4 treatments and 5 replications, namely substitution of wheat flour using purple sweet potato flour (P0 = 0%, P1 = 35%, P2 = 70%, P3 = 100%). The data obtained were analyzed using the ANOVA test (analysis of variance). Furthermore, to find out significant differences between treatments, Duncan's multiple range test was carried out. The results showed that the addition of purple sweet potato flour to the nuggets of the culled layers gave a significant effect on cooking loss, color, aroma, texture and taste but had no effect on the pH of the nuggets of the culled layers. Furthermore, the best value of organoleptic properties of culled chicken nuggets was in the 35% treatment using sweet potato flour. It can be concluded that to obtain good physical and organoleptic properties, the addition of purple sweet potato flour as much as 35%.